Calcium and integrin-binding protein 1-like interacting with an integrin α-cytoplasmic domain facilitates cellular immunity in Helicoverpa armigera. (June 2022) - Zhang, Ming-Ming; Luo, Ling-Ling; Liu, Yu; Wang, Gui-Jie; Zheng, Huan-Huan; Liu, Xu-Sheng; Wang, Jia-Lin
Abstract: Integrins are transmembrane receptor heterodimers composed of α and β subunits. They are known to mediate extracellular signals to promote cell adhesion and spreading, and are therefore essential for cellular immunity. However, proteins that bind to integrin cytoplasmic domains and mediate intracellular signaling to promote cell adhesion require identification. Calcium and integrin-binding protein 1 (CIB1) that binds to the integrin α-cytoplasmic domain has rarely been examined in insects. In this study, we found that 20-hydroxyecdysone promoted cell phagocytosis and spreading in Helicoverpa armigera . Transcriptomic analyses of hemocytes identified an integrin α gene ( HaINTα-PS1 ) whose expression could be induced by either 20-hydroxyecdysone injection or bead challenge. Isothermal titration calorimetry assays showed that H. armigera CIB1-like (HaCIB1-like) weakly bound to the cytoplasmic domain of HaINTα-PS1 in the presence of calcium. HaINTα-PS1 or HaCIB1-like knockdown inhibited hemocytic encapsulation and phagocytosis, and plasmatocyte spreading. Moreover, HaCIB1-like overexpression in a H. armigera epidermal cell line overexpanded cells and impaired cell phagocytosis. Thus, insect CIB1-like potentially interacted with integrin α-cytoplasmic domain and facilitated cell adhesion. This study enriches our understanding of the molecular mechanism underlying integrin-mediated cellular immunity in insects. Highlights: 20E stimulates cell spreading and cell phagocytosis. Either 20E injection or bead challenge induces the expression of HaINTα-PS1 and HaCIB1-like. HaINTα-PS1 or HaCIB1-like knockdown inhibits cell spreading and cellular immunity. HaCIB1-like weakly binds the HaINTα-PS1 cytoplasmic domain in the presence of Ca 2+ . HaCIB1-like overexpression induces overexpanded HaEpi cells and impairs cell phagocytosis.